Epistles of the Brethren of Purity. On the Natural Sciences: An Arabic Critical Edition and English Translation of EPISTLES 15-21 By Carmela Baffioni, ed. and trans. (Oxford: Oxford University Press in association with the Institute of Ismaili Studies, 2013. 969 pages.) (American Journal of Islam and Society, 2014)
One does not need to repeat the oft-stated observation that editing and translatingthe epistles of the Brethren of Purity (Ikhwan al-Safa’) will greatly enhanceour understanding of the pre-Avicennan period’s intellectual history ofthe philosophical sciences. Carmela Baffioni, senior research fellow at the Instituteof Ismaili Studies, which sponsors this project, is a leading specialiston the Brethren, having spent an illustrious career at Naples – twenty-fiveitems in the bibliography constitute her major contributions, alongside the editionsand translations she has contributed to this series. She has already editedand translated the epistles on logic in an earlier volume of this series – thoseepistles come immediately before the seven that are published here (out ofthe seventeen epistles that comprise the second section on the natural sciences)and are the culmination of the first section on the mathematical sciences. Thevolume immediately after on epistle 22 on animals has been published manytimes and is arguably one of the most famous of the Epistles: The Case of theAnimals versus Man before the King of the Jinns (published in this series inthe translation of Lenn Goodman and Richard MacGregor).With this highly useful and impressive volume, she has made a majorcontribution. This large volume (around 1,000 pages of English and Arabic)comprises a foreword by Nader el-Bizri (the project’s general editor); an ...